2(2x – 5) + 1 = x – 8 – 5x
2(2x-5) = -4x - 7 <<<< transfer 1 to the right side
4x - 10 = -4x - 7 <<<< multiply 2(2x-5) = 2(2x) - 2(5) or to distribute
8x = 3 <<< 4x + 4x = -7 + 10
thus,,,
x = 3 / 8
Problem
2(2x – 5) + 1 = x – 8 – 5x
Solution:
2(2x-5)+1=x-8-5x
=>4x-10+1=x-8-5x <---- remove the brackets with appropriate operation
=>4x-x+5x=10-1-8 <---- take all the x terms to the left and numbers to the
right
=>8x=1 <---- here you have simplified
=>x=1/8 <---- here you get the result
This is the solution actually.